Early Female Hatching is Related to Sex Differences in Biochemical and Hematological Parameters - Vicentini, T.I.; Junior, J.B. Matos; Boleli , I.C. (International Journal of Poultry Science, 2016)
We assessed whether earlier hatching time in female compared to male broilers is related to differences in the duration of the actual embryonic development and/or hatching period, hematological parameters and hatchling quality. Four-hundred and fifty fertile eggs were incubated at 37.25-37.47°C and 37.19-37.91°C from day 1 to 13 and from day 14 of incubation, respectively, with eggshell temperature of 37.27±0.36°C until day 13 and 37.46±0.14°C from day 14 of incubation, as well as 60% relative humidity for the entire incubation period. To verified female tendency to earlier hatching than male, duration of the incubation and its phases was determined within a 34 h hatching window (470 to 504 h). All other variables were analyzed during periods of 478-489 and 493-504 h for females and males, respectively. Incubation length, hatching times between internal and external pipping and internal pipping and hatch were longer and the eggshell was thinner in males. There were no differences in the duration of embryonic plus fetal development, time between external pipping, hatch body, yolk sac, heart, or lung weights, or in blood concentrations of ions, gases, or glucose between the sexes. However, RBC, Hb and MCHC were higher in males, whereas MCV and MCH were higher in females. In addition, males had lower total cholesterol and triglyceride concentrations in the blood, but higher concentrations of urea, uric acid and total protein when compared to females. Altogether, these results suggest that early hatching time tendency in females is associated with lower energetic and gas exchange hematological potential as well as with a thicker eggshell.